Development Of Sno2-Based Thick-Film Gas Sensor Using Screen-Printing Technique For Detection Of Ethanol Gas - Ahmad, Muhammad Yusri (2017)
Mesoporous SnO2 were synthesized via soft-template method by using cationic surfactant (cetyltrimethylammonium bromide: CTAB) as template and hydrated tin chloride (SnCl4.5H2O) as inorganic precursor to be used as gas sensing materials. The performance of selected thick-film sensor under various operating conditions was studied with different concentrations of ethanol gas between 100 ppm and 1000 ppm. Based on the detection performance and characterization study, the best result was obtained when as-prepared SnO2 was calcined at 400 °C with 5 depositing layers while the best formulation was paste B when 40 wt% of mesoporous SnO2 mixed with 60 wt% of hydroxypropyl cellulose and ethylene glycol were used. The performance of selected thick-film sensor (Sn-400-B-40-5) under various operating conditions was at the optimum when operating temperature was at 300 °C with the highest sensitivity of 84.6 for 1000 ppm of ethanol gas detection. The response and recovery times were recorded to be 36 s and 300 s respectively